Progress of Research in Negative Thermal Expansion Materials: Paradigm Shift in the Control of Thermal Expansion - Takenaka, Koshi (Frontiers in Chemistry, 2018)
To meet strong demands for the control of thermal expansion necessary because of the advanced development of industrial technology, widely various giant negative thermal expansion (NTE) materials have been developed during the last decade. Discovery of large isotropic NTE in ZrW2O8 has greatly advanced research on NTE deriving from its characteristic crystal structure, which is now classified as conventional NTE. Materials classified in this category have increased rapidly. In addition to development of conventional NTE materials, remarkable progress has been made in phase-transition-type NTE materials using a phase transition accompanied by volume contraction upon heating. These giant NTE materials have brought a paradigm shift in the control of thermal expansion. This report classifies and reviews mechanisms and materials of NTE to suggest means of improving their functionality and of developing new materials. A subsequent summary presents some recent activities related to how these giant NTE materials are used as practical thermal expansion compensators, with some examples of composites containing these NTE materials